If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-9 + -5x) = -176 (-9 * 4 + -5x * 4) = -176 (-36 + -20x) = -176 Solving -36 + -20x = -176 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -20x = -176 + 36 Combine like terms: -36 + 36 = 0 0 + -20x = -176 + 36 -20x = -176 + 36 Combine like terms: -176 + 36 = -140 -20x = -140 Divide each side by '-20'. x = 7 Simplifying x = 7
| 2(1.5c)+4=-1 | | 5(4+x)=50 | | (x+3)(x^2+9)=0 | | 13=7+n | | 5x-8(x+5)=/3-3x | | r^2-9r+6= | | 4x+2=-70-2x | | solvea=2b-cforb | | solvea=2b-cforb | | (x^2+x+3)(x-3)=0 | | -32=5x+2x-4 | | a=2b-cforb | | 2x^3+18x^2+16x= | | x-7y=35 | | 2x(-x+2)=0 | | 4.5+48=55x-2640 | | 0x^2-18x^2= | | 1x=3y-6 | | 4x-6y=-50 | | 2a+3b=34 | | -2.4x+0.1y=6.7 | | 3x+(-6)+8= | | s=k | | 1.2y+1.2=-2.4 | | -2.4x+0.1y= | | Y-4(-2)=3 | | 7(x-4)=9x-3(x+12) | | 13x-39y=-78 | | 7+-3b=1 | | 10-5x+7x=2x+10 | | 73=5w+17 | | 5x+5-4x=3 |